2008
DOI: 10.1124/jpet.107.131987
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol and Clozapine Differentially Affect the Expression of Arrestins, Receptor Kinases, and Extracellular Signal-Regulated Kinase Activation

Abstract: Dopamine and other G protein-coupled receptors (GPCRs) represent the major target of antipsychotic drugs. GPCRs undergo desensitization via activation-dependent phosphorylation by G protein-coupled receptor kinases (GRKs) followed by arrestin binding. Arrestins and GRKs are major regulators of GPCR signaling. We elucidated changes in expression of two arrestins and four GRKs following chronic (21 days) treatment with haloperidol (1 mg/kg i.p.) or clozapine (20 mg/kg i.p.) 2 or 24 h after the last injection in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 38 publications
4
43
2
Order By: Relevance
“…Indeed, animal studies have demonstrated that signaling molecules are targets of modification with antipsychotic treatment. Proteins downstream of cAMP-and MAPKassociated pathways are changed after acute and chronic antipsychotic treatment (Ahmed et al, 2008;Molteni et al, 2009). Additionally, the pharmacological activity of nicotine has been shown to act via these same signaling pathways (Mobascher and Winterer, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, animal studies have demonstrated that signaling molecules are targets of modification with antipsychotic treatment. Proteins downstream of cAMP-and MAPKassociated pathways are changed after acute and chronic antipsychotic treatment (Ahmed et al, 2008;Molteni et al, 2009). Additionally, the pharmacological activity of nicotine has been shown to act via these same signaling pathways (Mobascher and Winterer, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…GRK2 is widely expressed in the brain, including primary dopaminergic areas (Arriza et al, 1992) and can phosphorylate and regulate D1, D2, and D3 dopamine receptors in in vitro cellular systems (Tiberi et al, 1996;Iwata et al, 1999;Kim et al, 2001;Kabbani et al, 2002;Sedaghat et al, 2006;Banday et al, 2007). Indirect evidence for the role of this kinase in the regulation of dopamine receptors was provided by the observation of alterations in the GRK2 expression levels in the striatum of animals with experimental parkinsonism (Bezard et al, 2005), rats treated with antipsychotics (Ahmed et al, 2008b), and rats receiving long-term cocaine treatment (Schroeder et al, 2009). Whereas a deletion of the GRK2 gene in mice results in embryonic lethality, presumably as a result of cardiac hypoplasia , mice heterozygous for this mutation are viable and were used to investigate the role of GRK2 in dopamine receptor functioning .…”
Section: E ␤-Arrestins/g Protein-coupled Receptor Kinases: From Dopamentioning
confidence: 99%
“…Evolution endowed mammals with ϳ1000 different GPCRs (Römpler et al, 2007) that are phosphorylated by seven GRKs (Moore et al, 2007) and a number of other kinases (Budd et al, 2000;Naik et al, 2005;Luo et al, 2008) and interact with four arrestin subtypes (Gurevich and Gurevich, 2006b). Each tissue and cell has a unique complement of receptors (Penn et al, 2001), GRKs and arrestins (Penn et al, 2001;Gurevich et al, 2002;Ahmed et al, 2008a,b;Bychkov et al, 2008) that changes, sometimes quite dramatically, during development (Gurevich et al, 2002, disease (Ahmed et al, 2008a;Bychkov et al, 2008), and drug treatment (Ahmed et al, 2008b). To make matters even more complicated, phosphorylation of the same receptor at different sites (Pals-Rylaarsdam et al, 1997; Lee et al, 2000;Key et al, 2003;Jones and Hinkle, 2008), by different GRKs Ren et al, 2005;Luo et al, 2008), or even by the same GRK to different levels (Vishnivetskiy et al, 2007) generates functionally distinct receptor species that bind arrestins with different biological consequences.…”
mentioning
confidence: 99%